What's Critical about Vulnerability? Rethinking Interdependence, Recognition, and Power. (2016) - Petherbridge, Danielle
Abstract : Images of vulnerability have populated the philosophical landscape from Hobbes to Hegel, Levinas to Foucault, often designating a sense of corporeal susceptibility to injury, or of being threatened or wounded and therefore have been predominantly associated with violence, finitude, or mortality. More recently, feminist theorists such as Judith Butler and Adriana Cavarero have begun to rethink corporeal vulnerability as a critical or ethical category, one based on our primary interdependence and intercorporeality. However, many contemporary theorists continue to associate vulnerability with violence and finitude rather than providing an account of the normative theory that might underpin vulnerability as a critical category. In this article, I explore an alternative notion of vulnerability in relation to both a theory of power and a normative account that draws on recognition theory. My aim in this article is twofold: first, to examine the complexity of vulnerability and how it relates to forms of recognition; second, to outline how the notion of vulnerability can operate as the basis for critiquing objectionable forms of vulnerability. This is to consider vulnerability not only as an ethical or ontological question but as a political one, and shifts arguments about its abuse and entanglement with power and violence to the public political sphere.